A COMPARATIVE STUDY OF HARIDRADI CHURNA AND SHRANGYADI CHURNA IN MANAGEMENT OF BRONCHIAL ASTHMA - Mishra Sadhana; Satish Agrawal (International Journal of Applied Ayurved Research, 2017)
Bronchial asthma is very distressing disease of respiratory system producing dyspnoea & discomfort. The prevalence of disease is continuously on toll due to increasing pollution and faulty lifestyle habits. In initial stage, it is curable, but once the chronicity sets, it becomes difficult to cure. Based on its symptoms it can be well correlated with Tamaka Shwasa which is one of the prime disease of Pranvaha Srotas. Considering all these facts this study is an attempt to search better remedy from the natural resources with object of providing well effective and safe treatment along with measures and medicines to provide strength to pranavaha srotas. Literally it has been mentioned that Shrangyadi Churna and Haridradi churna have specific effect on Tamaka Shwasa. In the present work, effect of above two churnas has been evaluated with promising results.